Kinetics and mechanism of polysulfides formation by a reaction between hydrogen sulfide and orthorhombic cyclooctasulfur. (15th February 2019) - Avetisyan, Khoren; Buchshtav, Tamir; Kamyshny, Alexey
Abstract: A detailed study of kinetics of reaction between hydrogen sulfide and orthorhombic cyclooctasulfur at environmentally relevant conditions, which results in formation of inorganic polysulfides, was performed. Rates of reaction were measured as a function of pH, temperature and concentrations of S 2− and S 0 in airtight stirred batch reactor. Reaction was carried out at [S 0 ]/[S 2− ] < 0.1 in order to minimize a contribution of interfering reaction between orthorhombic cyclooctasulfur and polysulfides, which are stronger nucleophiles than sulfanide (HS − ). Reaction was found to follow the 0.28 order with respect to activity of hydroxyl anion and first order with respect to concentrations of both hydrogen sulfide and orthorhombic cyclooctasulfur. The reaction activation energy was found to be 69 kJ mol −1 . At conditions relevant for sulfidic marine sediments, the characteristic time of the reaction is c.a. 1 year. Relatively high activation energy of the reaction and distribution of polysulfide species testify to formation of polysulfides by a reaction between sulfanide and dissolved cyclooctasulfur rather than by direct nucleophilic dissolution of orthorhombic cyclooctasulfur.